Impact assessment of the organisational structure in the performance of corporate strategy: The case study of National Housing Corporation - Chilo, Fatuma (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University Dar es Salaam Campus College in partial fulfilment of the requirement for award of the degree of Master of Science in Human Resources Management